Biosensors based on laccase for detection of commercially reactive dyes - Munteanu, Florentina-Daniela (2010)
The results obtained using Trametes versicolor laccase modified graphite electrodes for detection of eleven different commercially reactive dyes are presented for the first time herein. The increase in current upon injection of the analyzed substrate was shown to be approximated by Michaelis–Menten type dependence. The calculated kinetic constants were used to evaluate the applicability of the laccase modified graphite electrode for the detection of reactive dyes in textile effluents.